Protective Mechanisms of Unsaponifiable Matter from Rice Bran Against Tert‐Butyl Hydroperoxide‐Induced Oxidative Damage in HepG2 Cells. Issue 4 (26th January 2016) - Ham, Hyeonmi; Lee, Yu Young; Park, Ji‐Young; Lee, Choonwoo; Kwak, Jieun; Kim, In‐Hwan; Lee, Junsoo
Abstract: Rice bran is rich source of phytochemicals, such as phytosterols, tocopherols, tocotrienols, policosanols, γ‐oryzanol, triterpene alcohol and other minor compounds. In this study, we investigated the mechanisms underlying the protective effects of unsaponifiable matter from rice bran on tert ‐butyl hydroperoxide (TBHP)‐induced oxidative stress in HepG2 cells. HepG2 cells were pretreated with different concentrations of USM (0–100 µg/mL) for 6 h and oxidative stress was induced by TBHP. The result indicated that pretreatment of HepG2 cells with USM significantly reduced TBHP‐induced oxidative damage, as determined by cell cytotoxicity and intracellular reactive oxygen species generations. USM activated nuclear factor‐erythroid 2‐related factor 2 (Nrf2) nuclear translocation and subsequently enhanced the expression of phase II detoxifying enzymes including heme oxygenase‐1, glutamate‐cysteine ligase catalytic subunit, and NADPH: quinine oxidoreductase‐1. These results suggest that USM‐mediated up‐regulation of phase II detoxifying enzymes via Nrf2‐signaling pathways may provide a pivotal mechanism for its hepatoprotective action. Practical Applications: Rice bran is a major byproduct of the rice milling process and is produced every year in an enormous amount in Korea. Rice bran is mainly used as animal feed, cooking oil, and cosmetics. It contains important bioactive compounds. This study provides biological evidence that supports the use of rice bran unsaponifiable matter (USM) in the prevention of oxidative damage. The assessment of the protective mechanism of rice bran USM against oxidative damage may give insight into its application as bioactive ingredients in the production and development of functional foods.